Los colectivos escolares en la transformación de de la edcacón básica. - Fernández, Victor Manuel; Miranda, Guadalupe; Agular, Elizabeth; Ortega, Víctor Mario; Barraza, Rodolfo; Martínez, Heriberto; Lopez, Lucio; Leon, Manuel; Ortiz, Francisco; Villegas, Cuauhtémoc (Nodos y Nudos, 2002)
NA